Influence of Different Beverages on the Color Stability of Nanocomposite Denture Base Materials - Emad Azmy (Hindawi Limited, 2021)
Background. The effect of beverages on nanocomposite denture base materials is neglected. Therefore, this study aimed to investigate the influence of different beverages (coffee, tea, cola, and mineral water) on the color stability of nanoparticles-modified denture base materials (DBMs). Materials and Methods. A total of 280 specimens (n = 10/group) were prepared from heat-polymerized acrylic resin modified with different concentrations (3% and 7%) of zirconium dioxide (nano-ZrO2), titanium dioxide (nano-TiO2), and silicon dioxide (nano-SiO2) nanoparticles, while 0% was taken as a control. Color change (∆E) of the specimens was evaluated after simulating 6-month immersion time in four commonly used beverages, coffee, tea, cola, and mineral water, as experimental groups. Color stability was measured using a spectrophotometer, and then values were converted to National Bureau of Standards units (NBS units). The one-way ANOVA test was applied to compare color change (ΔE) results followed by Bonferroni’s post hoc test (α = 0.05). Results. The results showed that the heat-polymerized acrylic resin modified with different types of nanoparticles showed lower color changes after being immersed in beverage solutions compared to the unmodified group (P < 0.001), so the color stability of heat-polymerized acrylic resin was significantly enhanced by the addition of several nanoparticles; nano-ZrO2 showed the lowest ΔE followed by nano-TiO2 and then nano-SiO2. Regardless of the filler type, 3% concentration showed lower mean ΔE than 7% concentration. Regarding the beverage solutions, the greatest color change was found in the coffee group followed by tea and cola, while water showed the least changes. Conclusion. Modification of heat-polymerized acrylic resin with certain amounts of nano-ZrO2, nano-TiO2, and nano-SiO2 may be useful in improving color stability.